NMOS-Based Integrated Modular Bypass for Use in Solar Systems (NIMBUS): Intelligent Bypass for Reducing Partial Shading Power Loss in Solar Panel Applications - Pieter Bauwens; Jan Doutreloigne (Energies, 2016)
NMOS-based Integrated Modular Bypass for Use in Solar systems (NIMBUS) is designed as a replacement for the traditional bypass diode, used in common solar panels. Because of the series connection between the individual solar cells, the power output of a photovoltaic (PV) panel will drop disproportionally under partial shading. Currently, this is solved by dividing the PV panel into substrings, each with a diode bypass placed in parallel. This allows an alternative current path. However, the diodes still have a significant voltage drop (about 350 mV), and due to the fairly large currents in a panel, the diodes are dissipating power that we would rather see at the output of the panel. The NIMBUS chip, being a low-voltage-drop switch, aims to replace these diodes and, thus, reduce that power loss. NIMBUS is a smart bypass: a completely stand-alone system that detects the failing of one or more cells and activates when necessary. It is designed for a 100-mV voltage drop under a 5-A load current. When two or more NIMBUS chips are placed in parallel, an internal synchronization circuit ensures proper operation to provide for larger load currents. This paper will elaborate on the operation, design and implementation of the NIMBUS chip, as well as on the first measurements.